Beyond the conceivable : studies on Germany, Nazism, and the Holocaust - Diner, Dan, 1946- (Weimar and now, 2000)
The major essays of Dan Diner, who is widely read and quoted in Germany and Israel, have been collected in this English edition. They reflect the author's belief that the Holocaust transcends traditional patterns of historical understanding and requires and epistemologically distinct approach.